Effects of 12 Weekly Folk Dance Studıes on Some Physıcal Suıtabılıty Parameters of Works of Dıfferent Local Area in Prımary School Age Chıldren - Erdal Tasgin; Metin Özlü; Evrim Çakmakçı (Türk Spor ve Egzersiz Dergisi)
In this study, it was aimed to determine the effect of Artvin region and Antep region folk dance program applied for 12 weeks on some physical fitness parameters on children at primary education level. The study aimed to examine the development of some of the motoric characteristics of folk dance studies of different regions applied in the 9-10 year old children two days a week. In Gaziantep region, 12 girls and 7 boys (Xage=10±0.61), totally 19 children, and Artvin region as 10 girls and 5 boys (Xage=10), totally 15 children participated in the study. Flexibility, Vertical Jumping, Stopping Long Jump, 20 m Sprint test values were evaluated before (pre-test) and end (test) 12 week application. For the analysis of the data, Wilcoxon t test was used in non-paramatic tests in SPSS 20 package program. There were significant differences in sit-in, vertical jump (p lt;0.05), stopping long-jump, and 20-meter sprint values while the Artvin group did not show any difference in weight values (p lt;0.05). In the Antep region, there were significant differences in weight, sit-reach, vertical jumping and 20 meters sprint values while the practice group did not show any difference in stopping long jump values (p lt;0.05). As a result, it has been observed that Artvin region and Antep region folk dances conducted for 12 weeks cause some physical values of children to develop and that the orientation of primary school children to folk dances has a positive and important effect for children.